State ownership, petroleum revenue, and the enduring legacy of authoritarianism in Angola - Pule, Ramakwe Nicholus (Department of Political Studies, 2021)
In the post-independence period, Angola's political economy has been shaped by the petroleum industry. After gaining independence in 1975, Angola turned authoritarian and subsequently, Sonangol, a state-owned oil company, was created. Once established, authoritarianism in Angola persisted for a long period, with oil playing a major role. This study investigates how the state's ownership of Sonangol has reinforced authoritarianism in Angola. Theoretically, it builds on the ideas of the resource curse hypothesis, which refers to the adverse effects of abundant non-renewable resources on a country's socio-economic and political outcomes. In addition to these findings of an adverse impact of non-renewable resources, this study argues that the type of resource ownership matters. Specifically, state ownership adversely affects political regimes. The rentier state model and the centralized political economy model of the resource curse are applied to investigate how the interaction between state ownership and petroleum revenue has reinforced authoritarian persistence in Angola. Building on Ross' quantitative cross-national findings of this interaction, this study uses process tracing research method to provide an in-depth investigation of Angola. There are two central findings. First, state ownership (with control) in the oil sector enabled the Angolan state to capture petroleum rents directly. This direct access to rents granted the state autonomy from having to formulate its goals under the scrutiny of its citizens, and thus undermined the statesociety bargaining dynamic. Second, the incumbent's discretionary power over the distribution of petroleum rents as patronage increased the value of staying in power and provided sufficient incentives for authoritarian practices to persist.